Hvis universitetet var en biotop: – et essay om forskningsetik - Kofoed, Jette (Tidsskrift for Professionsstudier, 2021)
In this essay I experiment with Lauren Berlant’s idea of ‘cruel optimism’ to investigate how policies of responsible conduct of research in academia have effects beyond efforts at establishing a spotless university. Based on experiences from teaching doctoral students about research integrity and ethics I unpack how culpa, vigilance and powerlessness surface. I suggest that there is a need to consider research ethics as an ethics that cares both for and about the university and for those grey areas that emerge when policies on responsible conduct of research are being introduced.